Effects of carp pituitary extract dosage on production of channel catfish, Ictalurus punctatus, female X blue catfish, I. furcatus, male hybrid fry. Issue 3 (2nd July 2016) - Kim, Soonhag; Su, Baofeng; Argue, Brad J.; Ligeon, Carel; Ramboux, Anne C.; Bart, Amrit N.; Dunham, Rex A.
ABSTRACT: Female channel catfish ( Ictalurus punctatus ) broodfish were injected with seven different dosages of carp pituitary extract (CPE) to induce ovulation. Eggs were fertilized with sperm from blue catfish ( Ictalurus furcatus ). The effects of CPE dosage on ovulation, eggs per kg of broodfish body weight (BW), fertilization rate, estimated hatching rate, and estimated fry production per kg of broodfish BW were determined. When the seven different dosages of CPE were considered, the dose (0, 11) (first injection, second injection mg/kg female BW) of CPE was inferior (P < .05) to the doses (2, 6), (2, 7), (2, 8), (2, 9), and (2, 10) for ovulation rate, fecundity, fertilization rate, hatch rate, and fry/kg. The doses (2, 6) and (2, 9) gave the highest (P < .05) mean percentages of ovulation, 100% and 97.0% respectively. The treatments (2, 8) and (2, 9) resulted in higher (P < .05) mean eggs per kg (7, 825 and 7, 323 respectively) than the doses (0, 11) and (3, 6, 3). The carp pituitary dosage had a dosage effect (P < .05) on the fertilization rate. The dose (2, 7) resulted in 78.1% fertilization, which was higher (P < .05) than the doses (0, 11), and (2, 6). The dose (2, 7) produced a higher (P < .05) mean, 69.5%, for estimated hatching than the treatments (0, 11), (2, 9), (2, 10), and (3, 6, 3). The doses (0, 11) and (3, 6, 3) had lower (P < .05) mean estimated fry per kg compared to the other five doses. The fish receiving dose (2, 7) had the highest observed fry per kg, 2, 788. As the spawning season progressed, the fry output increased until the final trial in late May. The results indicated that the dose (2, 8) currently recommended to catfish farmers for ovulating channel catfish is only appropriate early in the spawning season and that the treatments (2, 6) and (2, 7) are as effective or more effective once peak spawning is reached. During May, the dose used should be gradually reduced to obtain optimum fry output.